Enhancing Cell Block Quality- A Comparative Study Of Formalin And Agar-Based Methods - Mishra, Shruti; S., Kishore Kumar; Nag, Dipanwita (Annals of Pathology and Laboratory Medicine, 2020)
Background: There are not many studies conducted in India to compare cell block preparation methods with reagents and materials that are readily available in all laboratories. This study aimed to standardize and compare two simple cell block techniques, which can be done in low resource settings too. In the study, 35 cases of thyroid, lymph node, and breast were collected for both FNA and cell block preparation for six months. Materials and Methods: There were separate passes given for both methods. A total of seventy cell blocks made using formalin and agar methods of preparation. Results: We compared both the methods on technical and morphological levels. The formalin method was overall easy to perform and was yielding good morphological results in 98% cases, the only drawback being cell loss during handling and processing. While in the agar method, there was almost no cell loss, but it was more technically difficult and yielded poorer morphological results. A scoring system was made for cellularity: no cells = 0, hypo-cellular = 1+, hypo-cellular with tissue fragments = 2+, cellular = 3+.18 A score of 2+ and 3+ was scored by 31/35 formalin blocks and 28/35 agar blocks. Conclusions: The sensitivity of both formalin and agar methods are almost comparable. However, the procedure of the formalin method is far more straightforward and user friendly. Moreover, it also provides a better architectural picture than the agar method.